Supply Chain Risk Management in Food Industry: An IoT and ML Approach (International Journal of Food and Nutritional Sciences, 2021)
Supply Chain Risk Management (SCRM) in the food industry is of paramount importance due to the complexity and vulnerability of the global food supply chain. This abstract provides a concise overview of the challenges, solutions, and transformative potential of integrating Internet of Things (IoT) and Machine Learning (ML) technologies into SCRM practices within the food sector. The food supply chain faces multifaceted challenges, including food safety, supply chain complexity, environmental risks, and regulatory compliance. These challenges necessitate innovative risk management strategies. IoT technologies offer real-time data collection and monitoring capabilities, ensuring food safety and quality throughout the supply chain. Temperature sensors, GPS trackers, RFID tags, and other IoT devices enable continuous monitoring, reducing the risk of spoilage, contamination, and supply chain disruptions. ML, as a subset of artificial intelligence, empowers supply chain stakeholders with predictive analytics capabilities. ML algorithms forecast demand fluctuations, optimize inventory levels, and predict equipment failures, facilitating proactive risk mitigation. Quality control and compliance benefit from ML-based image recognition systems, swiftly identifying defects in food products. Supplier assessment and traceability are enhanced by ML algorithms evaluating supplier reliability and blockchain technology providing end-to-end traceability. These technologies contribute to sustainability efforts by optimizing resource utilization and minimizing waste. The integration of IoT and ML is transformative in SCRM within the food industry, offering real-time insights, predictive analytics, and quality control enhancements. Challenges remain, but the benefits are reshaping the industry's risk management landscape. Organizations investing in these technologies position themselves to thrive in an ever-changing food market while prioritizing consumer safety and product quality. Collaboration among stakeholders is vital to building resilient, efficient, and sustainable food supply chains